Assessing the Effectiveness of Administrative Services in Population and Civil Registration: Evidence from Gorontalo City - Asmari, Annisa; Rachman, Ellys; Antu, Yahya; Sahensyah luthfi (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to analyze the effectiveness of population administration services in Gorontalo City by highlighting three main aspects, namely responsiveness, quality of human resources, and service system. Theoretical framework: This study is based on public service theory and the principle of good governance, where service effectiveness is understood as a result of the interaction between responsiveness to community needs, human resource competence, and the use of technology in the service system. Literature review:  This study refers to the study of the effectiveness of public services, digitization of population administration, as well as the role of human resources and community complaints, while filling in the gaps of studies that rarely emphasize the integration of technical, institutional, and community participation aspects. Method: The study used a descriptive qualitative approach by triangulating data through interviews, observations, and documentation at the Gorontalo City Population and Civil Registration Office. Results: The results show that even though the digitization of services through the Centralized SIAK and the pick-up program has been implemented, the implementation has not been fully optimal. In the aspect of responsiveness, there are still obstacles in the form of long waiting times and limitations in handling public complaints. In terms of human resources, there is a competency gap in mastering technology and a lack of continuous training. Meanwhile, the service system still faces obstacles in the form of technical problems and low digital literacy of the community, which has an impact on the effectiveness of online services as a whole. Implications: This study emphasizes the need to increase human resource capacity, optimize service technology, and improve the public complaint system, with the support of synergy between technical, institutional, and community participation aspects to realize responsive and accountable administrative services. Novelty: The contribution of this research lies in the emphasis on the integration of digital innovation, strengthening human resource competence, and community participation as a strategy to improve the quality of population administration services in the region, especially in Gorontalo City.